Occupational therapy perspective on the attributes of interdependency among Malay older people in the community: an interpretative phenomenological analysis / Ahmad Shahir Abdul Mutalib - Abdul Mutalib, Ahmad Shahir (2016)
In Malaysia, evidence-based information regarding interdependency and its attributes among the Malay older people in the community is still limited and inconclusive. To explore this issue, Interpretative Phenomenological Analysis (IPA) approach was used to understand how older people in their context, makes sense of interdependence phenomenon by exploring how they ascribe meaning to their life experiences in their interactions with others in the community. A total of 11 participants were engaged from Melaka, Kuala Lumpur and Kota Bharu. Five main interdependent practices identified were issues regarding interpersonal relationships, living expenditure, housekeeping activities, implementation of festive and congregations, and travelling activities. The interdependence activity most frequently involved spouse, immediate and close family members. However, issues regarding housekeeping and travelling needs and activity may include friends and neighbours.